Docência compartilhada e prática docente num contexto interdisciplinar: desafios e contribuições na transição do 5º para o 6º ano do Ensino Fundamental - Nunes, Áurea Rodrigues (2018)
The present work refers to the "More Education São Paulo" Program, an educational policy that was implemented in 2014 in the city of São Paulo and promoted the reorganization of the Fundamental Education in learning cycles, with the objective of verifying the perception of teachers as well as the possible contributions of this practice to the transition from the fifth to the sixth year of elementary education, the theme of this production. It was developed from a qualitative approach, and presents as theoretical basis the studies of Freire (1996), Perrenoud (2000), Moll (2004), Rios (2010), Libâneo (2011), Fazenda (2008-2011-2013) , Beyer (2013), Tardif (2014) and André (1983), the latter being the basis for the analysis of the data obtained in the field research, which, together with a documentary research, compose this production. Such research indicates that the transition from the fifth to the sixth grade is still a difficult time for both students and teachers and that Shared Teaching is a way to mitigate this process and that its greatest contribution is in the fact that it makes possible the establishment of an initial bond between the teachers and the future students of the 6th grade. In addition, the research reveals that there is a need for investment in continuing education to guarantee the quality of teaching practice in this modality, as well as the perception and understanding of interdisciplinarity as the guiding thread of the teaching and learning process. It also reveals that the lack of time and space for planning presents itself as an impediment for Shared Teaching to be properly developed and effectively incorporated into the school project